2013
DOI: 10.1038/pcan.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

Health disparities in clinical practice patterns for prostate cancer screening by geographic regions in the United States: a multilevel modeling analysis

Abstract: Men living in urban areas and states with lower prevalence of doctors have lower odds of screening for prostate cancer and PSAT, respectively, after adjusting for individual variables. Future studies should examine the reasons for these health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Around half (18) of the included studies were from the United States (USA), followed by Australia (19), the United Kingdom (UK, 24), Canada (5), Spain (4), the Netherlands (3), New Zealand (3), Denmark (2), France (2), and Ireland (2). Seven more studies were also from Europe (one each from Belgium, Finland, Germany, Greece, Lithuania, Sweden, and Switzerland), five from Asia (two from Japan, one each from Iran, South Korea and Taiwan), two from other parts of North America (French West Indies, Puerto Rico), one from South America (Colombia), one from Africa (Egypt) and one including Australia and Canada (Supplemental File 3).…”
Section: Resultsmentioning
confidence: 99%
“…Around half (18) of the included studies were from the United States (USA), followed by Australia (19), the United Kingdom (UK, 24), Canada (5), Spain (4), the Netherlands (3), New Zealand (3), Denmark (2), France (2), and Ireland (2). Seven more studies were also from Europe (one each from Belgium, Finland, Germany, Greece, Lithuania, Sweden, and Switzerland), five from Asia (two from Japan, one each from Iran, South Korea and Taiwan), two from other parts of North America (French West Indies, Puerto Rico), one from South America (Colombia), one from Africa (Egypt) and one including Australia and Canada (Supplemental File 3).…”
Section: Resultsmentioning
confidence: 99%
“…The geographical and prostate cancer factors found in selected disparity studies have been summarized in the Table. [12][13][14][15][16][17][18][19][20][21][22][23][24][25]…”
Section: Resultsmentioning
confidence: 99%
“…52 In the field of prostate cancer, research using GIS approaches has been conducted to investigate diagnoses, management, and treatment outcomes across different geographical levels, such as counties, census division/tracts, cancer registry areas, and other aggregate geographical scales. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] Cockburn et al 53 used the GIS to geocode the historical residential addresses of individuals and measured the association between ambient exposure to pesticide and incidence rates of prostate cancer in California. They found a positive relationship between prostate cancer and ambient pesticide exposure in and around homes in intensely agricultural areas.…”
Section: Geographical Information System and Its Role In Disparity Rementioning
confidence: 99%
“…A smaller study (94 cases, 167 controls), which did not adjust for education level, found that circumcision conferred an increased risk of prostate cancer (OR 1.89, 95% CI 1.13–3.18) . This finding may have been attributable to a higher education level amongst cases, which is associated with a greater tendency to be circumcised and to undergo screening for prostate cancer by, either PSA screening and/or DRE .…”
Section: Discussionmentioning
confidence: 95%
“…In addition, men in the present study who were circumcised late in life had a lower education level than those circumcised earlier. Education is positively associated with being screened, and thus diagnosed for prostate cancer . However, as the protective effect of circumcision at a late age persisted after adjustment for education and diabetes, other factors appear to be at play.…”
Section: Discussionmentioning
confidence: 96%